Predicting organisational commitment: The role of line manager communication, employee trust and job satisfaction - Tatiana Ndlovu; Emmanuel S. Quaye; Yvonne K. Saini (South African Journal of Business Management, 2021)
Purpose: This study examines the influence of line manager communication (LMC) on affective organisational commitment through the mediating mechanisms of employee trust and job satisfaction. The study further investigates the moderation effect of line manager communication and employee trust to explain affective organisational commitment.